Base pay + (rate * sales) = total pay
b + r(400) = 388
b + r(700) = 454
b = 388 - 400r
now sub into 2nd equation
388 - 400r + 700r = 454
-400r + 700r = 454 - 388
300r = 66
r = 66/300
r = 0.22...22% is the rate
substitute for r
b + 400r = 388
b + 400(0.22) = 388
b + 88 = 388
b = 388 - 88
b = 300
so ur equation is : y = 0.22x + 300
y = 0.22(2600) + 300
y = 572 + 300
y = 872......so her salary when selling $2600 worth of stuff is $872
Answer:
c
Step-by-step explanation:
hope this helps
Answer:
x² - 10x + 21
Explanation:
To answer this question, we will simply multiply each term from the first bracket by each term from the second and then combine like terms to get the final expression.
This can be done as follows:
(x - 3)(x - 7)
x(x) + x(-7) -3(x) -3(-7)
x² - 7x - 3x + 21
x² - 10x + 21
Hope this helps :)
Answer:
4x^3 +10x
Step-by-step explanation:
for f(x) × g(x) you should multiply their functions :
(2x^2+5)×(2x) = 4x^3 +10x